Álevité – jiné pojetí islámu? - Kateřina Vytejčková (AntropoWebzin)
The Alevi are a religious minority in Turkey. It is a heterogeneous group including millions of Muslims who do not profess the major Sunni movement. During the time of the Ottoman Empire they were often persecuted as heretics. The Alevi and the Bektashi rise from the same origins which stretch back to the 13century to the theory of dervish Hadji Bektash Veli. In the first case it was concerned mainly rural inhabitants and in the second case it was concerned urban inhabitants – members and adherents of the dervish order Bektashi. Alevi Islam is called “Folk Islam”. It connects the elements of Shi’a Islam, Sufi movement, Christianity and pre- Islam systems of belief. The Alevi are despised by the major society because they do not stand aloof from drinking alcohol and they do not keep the Five Pillars of Islam which the orthodox Islam is based on. There was created a separate genre of anecdotes about the Alevi-Bektashi. This contribution introduces the main principles of their belief and ceremonies and brings also illustrations of some anecdotes.